DINAMIKA RESISTENSI PETANI TERHADAP EKSPANSI KAPITALISME DI JAWA (Studi atas Perlawanan Petani Terhadap Pertambangan Pasir Besi di Karangwuni Kulon Progo) - Suliadi Suliadi (Jurnal Sosiologi Reflektif, 2015)
This thesis is aimed to analyze the peasant resistance against the iron sand mining that occurred in Kulon Progo. As its starting point, this study is based on the change in political attitude of peasants, who were initially against it turned into approving to the iron sand mining. Through an approach of James C. Scott’s “moral economy of peasant” and Samuel L. Popkin’s “political economy”, this research is reviewed in descriptive analysis of how the change in political attitude of peasants eventually happen. With that analysis, this study shows that the changes in political attitudes of peasants in response to the expansion of mining capitalism is nothing more than a political compromise by the peasants in response to the expansion of mining capitalism. What is actually going to be refused is the ways of investors / companies and countries in expansion which is capitalist bias, which only creates a farming community becomes eliminated to access the available resources.